O08-2 Occupational exposure to benzene and alterations in immune/inflammatory markers. (1st September 2016) - Rothman, Nathaniel; Bassig, Bryan A; Zhang, Luoping; Vermeulen, Roel; Li, Guilan; Kemp, Troy J; Hu, Wei; Purdue, Mark P; Yin, Songnian; Rappaport, Stephen M; Shen, Min; Linet, Martha; et al.
Abstract : Introduction: Benzene is an occupational solvent that is used in multiple industries, and is a known human carcinogen (IARC Group 1) that is hematotoxic and causes acute myeloid leukaemia. Further, there is some evidence that occupational benzene exposure is associated with certain lymphoid neoplasms. To follow up these observations, we evaluated the relationship between occupational benzene exposure and levels of immune markers that were measured using a multiplex panel. Methods: A Luminex bead-based assay was conducted among 52 factory workers exposed to benzene and 31 unexposed workers that were enrolled in a cross-sectional molecular epidemiology study in China. Personal benzene exposure was repeatedly monitored in workers using a 3 M organic vapour passive monitoring badge before phlebotomy. Linear regression was used to evaluate differences in marker concentrations between benzene exposed vs. unexposed workers, and to explore exposure-response trends (unexposed, ≤5 ppm, >5 ppm). Results: Multiple markers were significantly altered in benzene exposed workers compared to unexposed workers (P-value < 0.05), including TNF-α (27% increase in exposed workers). Further, eight markers showed evidence of an exposure-response relationship. Among these, BCA-1 (45% reduction overall) and IL-17A (38% reduction overall) were significantly reduced in both lower and higher exposed workers compared to unexposed workers. Conclusions: Occupational exposure to benzene was associated with a range of immune perturbations including alterations in markers that regulate B-cell chemotaxis and regulation of cytotoxic T-cell activity. Notably, two of these markers (TNF-α and BCA-1) have previously been associated with risk of non-Hodgkin lymphoma in prospective studies. These observations provide additional biologic insight into the effects of benzene on the immune system.